Reassessment of the Phylogenetics of Two Pygmy Grasshopper Generic Groups ITetrix/I and ISystolederus/I through Mitochondrial Phylogenomics Using Four New Mitochondrial Genome Assemblies - Guan, De-Long; Huang, Chao-Mei; Deng, Wei-An (Insects (Basel, Switzerland), 2024)
Pygmy grasshoppers are a highly diverse group of insects that are distributed across China’s landscapes. Their small size, limited flight capabilities, and reliance on humid habitats make them an intriguing subject to study evolution and biodiversity patterns. This research focused on improving the phylogenetic classification system of pygmy grasshoppers, which relies heavily on physical traits that can sometimes be misleading. We sequenced the complete mitochondrial DNA of four pygmy grasshopper species to reconstruct the evolutionary relationships among these species. Comparative analyses of new and existing DNA data revealed conflicts regarding the breadth of two generic groups—Systolederus and Tetrix. The Systolederus generic group encompasses too much diversity, necessitating taxonomic divisions, while Tetrix diversity appears restricted by overly splitting similar species. Further assessments uncovered over 150 million years of pygmy grasshopper ancestry and evidence for rapid habitat colonization abilities in the Tetrix generic group. By integrating genetic data, we refined perspectives on the evolutionary affinities of these insects. This approach demonstrates the importance of coupling morphological and molecular techniques for robust biodiversity assessments amidst the intricacies of adaptation and convergence. Resolving such taxonomic limitations will strengthen future initiatives to document and preserve pygmy grasshopper diversity across changing landscapes. Mitochondrial genomes offer pragmatic genetic markers to reconstruct evolutionary relationships and inform taxonomic classifications. Here, we present complete mitochondrial sequences for four Chinese pygmy grasshoppers (Tetrigidae), aiming to reevaluate phylogenetic patterns and morphological taxonomy. Our 17,643 bp, 16,274 bp, 15,086 bp, and 15,398 bp mitogenomes of Exothotettix guangxiensis, Formosatettix longwangshanensis, Euparatettix sinufemoralis and Systolederus zhengi, respectively, exhibit archetypal Tetrigidae architecture. We constructed phylogenies using 13 protein-coding loci from 39 Tetrigidae mitogenomes, revealing several genus-level clusters with statistically solid support, conflicts regarding Ex. guangxiensis, F. longwangshanensis merging into Tetrix, and two subclades of Systolederus. The dated divergence analysis indicates over 150 Mya of Tetrigidae ancestry, tracing the Systolederus generic group splits up to ~75 million years ago. Moreover, the Tetrix generic group radiated over 14 Mya across vast distributions, consistent with rapid adaptive dispersals. Our mitochondrial reconstructions suggest that Synstolederus is taxonomically overextended for a single genus, while the distinctiveness of Ex. guangxiensis and F. longwangshanensis from Tetrix appears questionable, and the Tetrix generic group comprises a potential tRNA-Ile coding region. Our integrative mitogenomic approaches will help resolve issues stemming from morphological taxonomy that is reliant on traits that are prone to convergence. This investigation enhances comprehension of Tetrigidae phylogeny and accentuates molecular systematics.